Studying the Effect of Stratified Fluid on the Resistance and Flow Field of the KVLCC2 Tanker and DARPA Suboff using CFD - زيدان, أماني; نوار عباس (Latakia University Journal -Engineering Sciences Series, 2024)
This research aims to study the effect of stratified fluid on the resistance and flow field of ships and submarines. The influence of different speeds, drift angles, and positions of the internal surface on the resistance, the velocity field in the propeller plane, and the pressure field on the hull was studied. The CFD, URANS method, and the k-ω Shear Stress Transport (SST) model with the ANSYS program were used to solve the Navier-Stokes equations. The Volume of Fluid method was used to capture the internal surface between stratified fluid layers. The study was carried out on a KVLCC2 model and a DARPA Suboff model. The numerical results were compared with the experimental ones, which agreed well. The effect of the presence of the stratified fluid on both the resistance and the flow field around these marine vehicles was then studied. The results confirmed that sailing a ship or submarine within a stratified fluid will inevitably lead to an increase in resistance and affect the flow field's characteristics around the vehicle's hull. The study proved that submarines are less affected by stratified fluid than ships due to their streamlined shape.